SPECIATION AND CHARACTERIZATION OF ARSENIC IN GOLD ORES AND CYANIDATION TAILINGS USING X-RAY ABSORPTION SPECTROSCOPY - Paktunc D.; Foster A.; Heald S.; Laflamme G. (My University, 2004)
The knowledge of mineralogy and molecular structure of As is needed to better understand the stability of As in wastes resulting from processing of gold ores. In this study, optical microscopy, scanning electron microscopy, electron microprobe, X-ray diffraction and X-ray absorption fine structure (XAFS) spectroscopy (including both XANES and EXAFS regimes) were employed to determine the mineralogical composition and local coordination environment of As in gold ores and process tailings from bench-scale tests designed to mimic a common plant practice. Arsenic-bearing minerals identified in the ores and tailings include iron (III) oxyhydroxides, scorodite (FeAsO4·2H2O), ferric arsenates, arseniosiderite (Ca2Fe3(AsO4)3O2·3H2O), Ca-Fe arsenates, pharmacosiderite (KFe4(AsO4)3(OH)4·6–7H2O), jarosite (K2Fe6(SO4)4(OH)12) and arsenopyrite (FeAsS). Iron (III) oxyhydroxides contain variable levels of As from trace to about 22 wt% and Ca up to approximately 9 wt%.